PUBLIC MANAGEMENT OF SUSTAINABLE DEVELOPMENT OF TERRITORIES - Semenchuk , Tetiana; Postika , Bohdan (Collection of scientific papers «ΛΌГOΣ», 2023)
In recent decades, sustainable development issues have become increasingly relevant in the context of growing problems associated with the negative impact of human activity on the environment and social sphere. Public administration is proving to be a key tool in implementing strategies and policies aimed at sustainable growth and environmental restructuring. However, many issues remain unresolved, and more research is needed to find out how public governance can be optimised to achieve sustainable development.